Information Technology Governance Analysis Using COBIT 5 Framework: (Case Study : PLANT Division PT Pamapersada Nusantara) - Kelvin Kurniawan; Kusuma Adi Achmad; Satria Akbar Mugitama (School of Computing, Telkom University, 2023)
PT Pamapersada Nusantara or better known as PAMA is a subsidiary of PT United Tractors Tbk. There are several divisions in PAMA, one of which is the PLANT Division which is the focus of this research. To improve this performance, a special Information Technology System was created for employees. In order for application development to run better and in line with the company, an analysis is carried out which is expected to be a benchmark and company recommendation to optimize the information system. The analysis was carried out using the COBIT 5 framework method, the researcher focused on the MEA01 (Monitor, Evaluate, Assess Performance and Conformance) domain. Then for the method is observation and interview, researchers use this method to be able to collect accurate data With this method, researcher can provide recommendations regarding the results of the IT governance analysis to ensure and optimize that the information system runs according to the company’s wishes based on the COBIT 5 framework standardization. The average result obtained is level 3 for the current condition and level 4 for the expected condition. The recommendation of this study is that companies can implement regular monitoring SOPs on existing IT management and governance.